2019
DOI: 10.18332/tpc/112719
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the risk of tobacco use in pregnancy and factors associated with tobacco use in rural areas of Myanmar

Abstract: INTRODUCTION Tobacco use is recognized as the most important preventable risk factor for pregnancy complications and undesirable fetal outcomes. This study examined the reported prevalence of tobacco use among married men and women residing in rural areas, and their knowledge on the risks of tobacco use during pregnancy and the factors associated with tobacco use. METHODS A cross-sectional study was conducted within 32 villages in the delta region of Myanmar, randomly selected through multistage sampling proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…La mayoría de embarazadas y parejas creen que la información por sí sola no es suficiente para la cesación. Aunque, al igual que en un estudio previo 20 , las mujeres denotan una baja percepción de riesgo asociado al consumo de estas sustancias durante el embarazo, lo que podría atribuirse a una falta de información o comunicación inadecuada de la misma. Las mujeres y parejas expresan su preferencia por información no focalizada en aspectos negativos del consumo.…”
Section: Discussionunclassified
“…La mayoría de embarazadas y parejas creen que la información por sí sola no es suficiente para la cesación. Aunque, al igual que en un estudio previo 20 , las mujeres denotan una baja percepción de riesgo asociado al consumo de estas sustancias durante el embarazo, lo que podría atribuirse a una falta de información o comunicación inadecuada de la misma. Las mujeres y parejas expresan su preferencia por información no focalizada en aspectos negativos del consumo.…”
Section: Discussionunclassified
“…-Cut-off points were based on the grading system used by Show K et al 12 Total scores for both knowledge and attitude ranged from 0 to 5 and a higher score above the median value indicated good knowledge and attitude towards SHS.…”
Section: Research Tools and Measurement Methodsmentioning
confidence: 99%
“…11 One study conducted in the Ayarwaddy Region of Myanmar stated that 16% of current smokers reported the presence of a pregnant woman in their smoking area. 12 Another study in Myanmar reported that SHS exposure at home is higher in females (57.8%) than in males (52.0%). As for the exposure at workplaces, there are 71.9% in males and 54.7% in females.…”
Section: Introductionmentioning
confidence: 96%
“…13 One study conducted in the Ayarwaddy Region of Myanmar stated that 16% of current smokers reported the presence of a pregnant woman in their smoking area. 14 Another study in Myanmar reported that SHS exposure at home is higher in female (57.8%) than in male (52.0%) participants. As for the exposure at workplaces, there are 71.9% in male participants and 54.7% in female participants.…”
Section: Introductionmentioning
confidence: 96%